A feasibility study of image registration using volumetrically classified, motion-free bony landmarks in thoracic 4DCT images for image-guided patient setup. (29th March 2012) - Li, Guang; Xie, Huchen; Ning, Holly; Citrin, Deborah; Capala, Jacek; Cheng, Jason; Arora, Barbara C.; Coleman, C. Norman; Camphausen, Kevin; Miller, Robert W.
As rigid image registration becomes unreliable in the presence of involuntary organ motion, we present a novel approach to register CT images using stable bony landmarks for image-guided patient setup. Using 3D Volumetric Image Registration (3DVIR) technique, bony anatomy is volumetrically-classified as registration landmark, while soft tissues are ignored. Based on 4DCT, it was found that the spine, posterior ribs and clavicles do not move with respiration and remain registered throughout the breathing cycle. However, mutual information based registration produces an error of 1–2 mm due to moving soft tissues. It is suggested that the 3DVIR can improve image-guided setup.